ANTERIOR ABDOMINAL WALL ENDOMETRIOMA: A DIAGNOSTIC CHALLENGE - Khan, Salamat; Bhasyal, Krishna; Timilsina, Bhusan Raj (Journal of Universal College of Medical Sciences, 2016)
We are reporting a case of abdominal wall endometrioma (AWE) in a 32-year-old woman who had an 8 months history of lower abdominal pain and lump. The physical examination revealed an ill-defined mass without tenderness. Computed tomography (CT) showed an enhancing is odense mass at the level of umbilicus right to mid line in right rectus abdominis muscle. The patient was treated with a wide radical resection with a 1 cm margin. There was no postoperative complication. The histological examination confirmed endometriosis. The patient is now on regular follow-up and doing well without any recurrence, five months after her operation. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Page: 44-46